Analysis of elementary teachers’ challenges in implementing Kurikulum Merdeka in social studies - Rosvilani Saragih; Restu Restu; Mulyono Mulyono (Inovasi Kurikulum, 2025)
The implementation of the Kurikulum Merdeka in elementary schools requires teachers to have innovation and adaptation competencies, particularly in social studies learning. It emphasizes student-centered learning and allows teachers the freedom to choose learning methods and media. However, during its implementation, teachers face various challenges that need to be identified in order to improve the quality of learning. This study aims to describe the problems faced by teachers in implementing the Kurikulum Merdeka in social studies learning and examine the role of supervision at Gugus Dua Bintang Bayu Elementary School. The method used is a descriptive qualitative approach, with data collected through interviews, observations, questionnaires, and documentation involving teachers and the principal. The results indicate that the main challenges for teachers include low competency in learning innovation, limited understanding of the curriculum, lack of technology as a learning medium, difficulties in developing learning tools such as lesson plans and modules, and inadequate facilities and learning resources. Existing supervision is more administrative in nature and lacks ongoing practical guidance. These findings emphasize the importance of increasing teacher capacity and strengthening supervision for effective implementation of the Kurikulum Merdeka.   Abstrak Penerapan Kurikulum Merdeka di sekolah dasar yang menuntut guru memiliki kompetensi inovasi dan adaptasi, khususnya dalam pembelajaran IPS menekankan pembelajaran berpusat pada murid dan memberi kebebasan pada guru dalam memilih metode dan media pembelajaran. Namun, pada pelaksanaannya guru dihadapi dengan berbagai tantangan yang perlu diidentifikasi untuk meningkatkan kualitas pembelajaran. Penelitian ini bertujuan mendeskripsikan masalah yang dihadapi guru dalam implementasi Kurikulum Merdeka pada pembelajaran IPS serta mengkaji peran supervisi di SD Gugus Dua Bintang Bayu. Metode yang digunakan adalah deskriptif kualitatif dengan pengumpulan data melalui wawancara, observasi, angket, dan dokumentasi yang melibatkan guru dan kepala sekolah. Hasil menunjukkan bahwa tantangan utama guru meliputi rendahnya kompetensi inovasi pembelajaran, pemahaman kurikulum yang terbatas, kekurangan teknologi sebagai media pembelajaran, kesulitan dalam menyusun perangkat pembelajaran seperti RPP dan modul, serta fasilitas dan sumber belajar yang kurang memadai. Supervisi yang ada lebih bersifat administratif dan kurang memberikan bimbingan praktis berkelanjutan. Temuan ini menegaskan pentingnya peningkatan kapasitas guru dan penguatan supervisi agar implementasi Kurikulum Merdeka berjalan efektif. Kata Kunci: implementasi Kurikulum Merdeka; pembelajaran IPS; tantangan guru